The Chapter on Minerva of Rodrigo Caro’s Book Veterum Hispaniae deorum manes sive reliquiae: Edition, Translation and Commentary (Minerva, 2017)
This is the first edition, translation and commentary of the chapter on Minerva (identified with Pallas and Bellona) of Caro’s treatise on the ancient gods of Hispania, which is preserved in Oxford in an autograph manuscript of the Bodleian Library (Ms. D’Orville 47.). The author tells us of an island consecrated to Minerva on the Levantine coast according to Avienus, and of a sanctuary in a city near Malaga according to Strabo. He copies seven Latin inscriptions, although just those from Barcelona, Niebla and Los Molares are authentic, offering some valuable transcriptions of the latter two. He comments the images of the goddess in a misinterpreted coin of the city of Searo, and in an oil lamp, which he explains in the light of a Greek epigram attributed to Homer. He quotes Cicero’s text on Coria as an epithet of Minerva, which he relates unwisely to the Spanish place name Coria. As evidence of Minerva’s predilection for Spain, only after Greece and Italy, he mentions twenty ancient writers, the Academy founded in Osca by Sertorius in the first century BC, and eight humanists related, in a greater or lesser degree, to the University of Salamanca.
Keywords: Mythology; religion; epigraphy; numismatics; toponymy; humanism; Rodrigo Caro; Minerva